2014
DOI: 10.1371/journal.pone.0110194
|View full text |Cite|
|
Sign up to set email alerts
|

Onecut1 and Onecut2 Play Critical Roles in the Development of the Mouse Retina

Abstract: The entire repertoire of intrinsic factors that control the cell fate determination process of specific retinal neurons has yet to be fully identified. Single cell transcriptome profiling experiments of retinal progenitor cells revealed considerable gene expression heterogeneity between individual cells, especially among different classes of transcription factors. In this study, we show that two of those factors, Onecut1 and Onecut2, are expressed during mouse retinal development. Using mice that are deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 43 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…Using the NCBI BLAST tool, this probe sequence produced a 99% alignment to predicted chick sequence ChEST736n4, as well as high alignment scores (>90%) for the gene Onecut2 (OC2) in a variety of animals. Onecut2, which has been shown to be expressed by HCs in the mouse, results in a loss of 50% of the HCs when removed from mice (Goetz, Martin, Chowdhury, & Trimarchi, 2014;Sapkota et al, 2014). To examine the expression pattern further in the chick retina, we completed ISH and found expression of ChEST736n4 within a subset of cells in the ONBL at E4 (Figure 8l), much like the expression of Cath5 and Fgf19 at that timepoint.…”
Section: During Our Investigation Into the Genes Highly Expressed By E4mentioning
confidence: 92%
See 1 more Smart Citation
“…Using the NCBI BLAST tool, this probe sequence produced a 99% alignment to predicted chick sequence ChEST736n4, as well as high alignment scores (>90%) for the gene Onecut2 (OC2) in a variety of animals. Onecut2, which has been shown to be expressed by HCs in the mouse, results in a loss of 50% of the HCs when removed from mice (Goetz, Martin, Chowdhury, & Trimarchi, 2014;Sapkota et al, 2014). To examine the expression pattern further in the chick retina, we completed ISH and found expression of ChEST736n4 within a subset of cells in the ONBL at E4 (Figure 8l), much like the expression of Cath5 and Fgf19 at that timepoint.…”
Section: During Our Investigation Into the Genes Highly Expressed By E4mentioning
confidence: 92%
“…Initially discovered in subsets of developing murine single cells, studies of OC1-and OC2-deficient mice revealed that these genes are required for the generation of HCs (Goetz et al, 2014;Sapkota et al, 2014;Wu et al, 2013). However, the Onecut factors are not purely limited to expression in mature HCs, as further investigation showed that OC1 is a part of a regulatory network that biases Olig21 RPCs toward a HC fate (Emerson et al, 2013;Hafler et al, 2012).…”
Section: Single Cell Profiles Of Potentially Neurogenic Progenitor mentioning
confidence: 99%
“…Sequences (between 650 and 800bp in length) were amplified by PCR from isolated mouse cDNA (see supplemental table for details). Probes were visualized using an α-DIG-AP antibody (Roche) and subsequent exposure using BCIP and NBT Goetz et al 2014b). The 3'-targeted Plk3 probe used in this study was from the BMAP collection, accession number AW488956, the sequence for which was confirmed before use.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Microarray hybridization was performed as described previously (Goetz et al, 2014b further analysis was performed as described . The…”
Section: Microarraysmentioning
confidence: 99%
See 1 more Smart Citation